Antimicrobial multiresistance in microorganisms of the Enterobacterales order isolated from exotic passerines from farms in the Metropolitan Region of Fortaleza - L. S. Melo; A. J. F. Beleza; A. R. Marques; B. P. Lima; C. C. Fontão; C. D. S. Ribeiro; C. H. G. Nogueira; C. M. P. Freitas; L. B. S. Lemos; N. M. Pascoal Filho; R. S. C. Teixeira; W. C. Maciel (Brazilian Journal of Biology)
Abstract The aim of this study was to assess the degree of antimicrobial resistance in strains of the Enterobacterales order isolated from exotic passerine birds originated from breeding facilities in the metropolitan region of Fortaleza. For this purpose, 104 strains of ten different bacterial species were used. To perform the antibiogram, ten antibiotics from eight pharmacological classes were employed. Among the main results, a high resistance rate was found for some antimicrobials, notably ampicillin (91.35%) and sulfamethoxazole-trimethoprim (47.12%). Additionally, relevant rates of resistance were also found for meropenem, a controlled-use antibiotic. Concerning the bacterial species, Escherichia coli showed resistance to nine out of the ten tested antibiotics, and out of the 24 strains used, eight showed resistance to at least three antibiotics, classified as multidrug-resistant. Thus, the results presented reinforce the need for surveillance regarding multidrug-resistant strains because, besides causing harm to animal health, they could also become a public health problem due to the zoonotic potential that some strains possess.